Zanubrutinib Versus Ibrutinib in Symptomatic Waldenström Macroglobulinemia: Final Analysis From the Randomized Phase III ASPEN Study - Dimopoulos, Meletios A; Opat, Stephen; D'Sa, Shirley; Jurczak, Wojciech; Lee, Hui-Peng; Cull, Gavin; Owen, Roger G; Marlton, Paula; Wahlin, Björn E; Garcia-Sanz, Ramon; McCarthy, Helen; Mulligan, Stephen; et al. (Journal of clinical oncology, 2023)
The phase III ASPEN study demonstrated the comparable efficacy and improved safety of zanubrutinib versus ibrutinib in patients with Waldenström macroglobulinemia (WM). Here, we report long-term follow-up outcomes from ASPEN. The primary end point was the sum of very good partial response (VGPR) + complete response (CR) rates; secondary and exploratory end points were also reported. Cohort 1 comprised 201 patients (myeloid differentiation primary response 88-mutant WM: 102 receiving zanubrutinib; 99 receiving ibrutinib); cohort 2 comprised 28 patients (myeloid differentiation primary response 88 wild-type WM: 28 zanubrutinib; 26 efficacy evaluable). At 44.4-month median follow-up, VGPR + CR rates were 36.3% with zanubrutinib versus 25.3% with ibrutinib in cohort 1 and 30.8% with one CR in cohort 2. In patients with CXC motif chemokine receptor 4 mutation, VGPR + CR rates were 21.2% with zanubrutinib versus 10.0% with ibrutinib (cohort 1). Median progression-free survival and overall survival were not reached. Any-grade adverse events (AEs) of diarrhea (34.7% v 22.8%), muscle spasms (28.6% v 11.9%), hypertension (25.5% v 14.9%), atrial fibrillation/flutter (23.5% v 7.9%), and pneumonia (18.4% v 5.0%) were more common with ibrutinib versus zanubrutinib; neutropenia (20.4% v 34.7%) was less common with ibrutinib versus zanubrutinib (cohort 1). Zanubrutinib was associated with lower risk of AE-related treatment discontinuation. Overall, these findings confirm the long-term response quality and tolerability associated with zanubrutinib.
Keywords: Piperidines; Pyrimidines; lidé; piperidiny; Waldenstrom Macroglobulinemia; Waldenströmova makroglobulinemie; Humans; pyrimidiny